Reactive Human Plasma Glutathione Peroxidase Mutant with Diselenide Bond Succeeds in Tetramer Formation - Zhenlin Fan; Qi Yan; Jian Song; Jingyan Wei (MDPI AG, 2022)
Plasma glutathione peroxidase (GPx3) belongs to the GPx superfamily, and it is the only known secreted selenocysteine (Sec)−containing GPx in humans. It exists as a glycosylated homotetramer and catalyzes the reduction of hydrogen peroxide and lipid peroxides, depending on the Sec in its active center. In this study, a previously reported chimeric tRNAUTuT6 was used for the incorporation of Sec at the UAG amber codon, and the mature form of human GPx3 (hGPx3) without the signal peptide was expressed in amber−less E. coli C321.ΔA.exp. Reactive Sec−hGPx3, able to reduce H2O2 and tert−butyl hydroperoxide (t−BuOOH), was produced with high purity and yield. Study of the quaternary structure suggested that the recombinant Sec−hGPx3 contained an intra−molecular disulfide bridge but failed to form tetramer. Mutational and structural analysis of the mutants with three Cys residues, individually or jointly replaced with Ser, indicated that the formation of intra−molecular disulfide bridges involved structure conformational changes. The secondary structure containing Cys77 and Cys132 was flexible and could form a disulfide bond, or form a sulfhydryl-selenyl bond with Sec49 in relative mutants. Mutation of Cys8 and Cys132 to Sec8 and Sec132 could fix the oligomerization loop through the formation of diselenide bond, which, in turn, facilitated tetramer formation and noticeably improved the GPx activity. This research provides an important foundation for the further catalysis and functional study of hGPx3.